Integration of bioinformatics and imaging informatics for identifying rare PSEN1 variants in Alzheimer's disease. Issue 1 (August 2016) - Nho, Kwangsik; Horgusluoglu, Emrin; Kim, Sungeun; Risacher, Shannon; Kim, Dokyoon; Foroud, Tatiana; Aisen, Paul; Petersen, Ronald; Jack, Clifford; Shaw, Leslie; Trojanowski, John; Weiner, Michael; et al.
Abstract Background Pathogenic mutations inPSEN1 are known to cause familial early-onset Alzheimer's disease (EOAD) but common variants inPSEN1 have not been found to strongly influence late-onset AD (LOAD). The association of rare variants inPSEN1 with LOAD-related endophenotypes has received little attention. In this study, we performed a rare variant association analysis ofPSEN1 with quantitative biomarkers of LOAD using whole genome sequencing (WGS) by integrating bioinformatics and imaging informatics. Methods A WGS data set (N = 815) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort was used in this analysis. 757 non-Hispanic Caucasian participants underwent WGS from a blood sample and high resolution T1-weighted structural MRI at baseline. An automated MRI analysis technique (FreeSurfer) was used to measure cortical thickness and volume of neuroanatomical structures. We assessed imaging and cerebrospinal fluid (CSF) biomarkers as LOAD-related quantitative endophenotypes. Single variant analyses were performed using PLINK and gene-based analyses of rare variants were performed using the optimal Sequence Kernel Association Test (SKAT-O). Results A total of 839 rare variants (MAF < 1/√(2 N) = 0.0257) were found within a region of ±10 kb fromPSEN1 . Among them, six exonic (three non-synonymous) variants were observed. A single variant association analysis showed that thePSEN1 p. E318G variant increases the risk of LOAD only in participants carryingAPOE ε4 allele where individuals carrying the minor allele of thisPSEN1 risk variant have lower CSF Aβ1–42 and higher CSF tau. A gene-based analysis resulted in a significant association of rare but not common (MAF ≥ 0.0257)PSEN1 variants with bilateral entorhinal cortical thickness. Conclusions This is the first study to show thatPSEN1 rare variants collectively show a significant association with the brain atrophy in regions preferentially affected by LOAD, providing further support for a role ofPSEN1 in LOAD. ThePSEN1 p. E318G variant increases the risk of LOAD only inAPOE ε4 carriers. Integrating bioinformatics with imaging informatics for identification of rare variants could help explain the missing heritability in LOAD.